Chemical and genomic analyses of polycyclic aromatic hydrocarbon biodegradation in Sphingobium barthaii KK22 reveals divergent pathways in soil sphingomonads. (July 2020) - Maeda, Allyn H.; Nishi, Shinro; Hatada, Yuji; Ohta, Yukari; Misaka, Kanna; Kunihiro, Marie; Mori, Jiro F.; Kanaly, Robert A.
Abstract: Polycyclic aromatic hydrocarbons (PAHs) are hazardous pollutants that are biodegraded by soil bacteria and the soil sphingomonads are thought to be major contributors to PAH biodegradation. To predict PAH environmental fates it is necessary to understand the chemistry and genetics of PAH biodegradation by sphingomonads. When the soil sphingomonad Sphingobium barthaii KK22 was exposed to low molecular weight (LMW) PAHs and biotransformation products were investigated by comprehensive chemical analyses, at least twenty products were identified by different techniques and both intradiol- and extradiol-aromatic ring cleavage pathways were found to be active in this organism. Sphingomonads, a large and diverse group, have been studied in regard to PAH biodegradation, however intradiol-ring cleavage of LMW PAHs has never been reported. Whole genome sequencing and prediction of S. barthaii KK22 functional genes revealed sets of aromatic ring-hydroxylating oxygenases and PAH biotransformation genes. Combined with chemical analyses results, novel, near complete PAH biotransformation pathways for soil sphingomonads were constructed. In conjunction with quantitative assays, a comprehensive view of PAH biodegradation was obtained that revealed divergent downstream pathways that advanced our understanding of the PAH biotransformation capabilities of these versatile soil bacteria and shall aid in predictions of PAH environmental fate during soil bioremediation. Graphical abstract: Image 1 Highlights: Soil sphingomonads are considered major contributors to hazardous pollutant PAH biodegradation. Comprehensive LC/ESI-MS/MS analyses identifies new LMW PAH products from soil sphingomonad. Novel divergent intradiol pathways for LMW PAH biodegradation proposed for sphingomonads. Chemical and genomic analyses provide comprehensive view of LMW PAH biodegradation by new species.